Factors Influencing Companies to Stay Private: A Case Study from Maldives - Safna, Hawwa (2014)
In the Maldives, due to the high pressure to earn more because of the high living costs, the people are in need of investment opportunities and stock market seems to be a very appropriate choice. However, there are very limited or no investment opportunities available on the Maldivian Stock Exchange. It is believed that the capital market of the Maldives has a lot of potential to grow and develop and among that a significant part is the stock market. The stock market of the country is under-developed and the main reason for this is the unwillingness of the private companies to go public even though there is the potential and capability. This research attempts to find out the factors which hold back the companies in the Maldives from going public and looks into ways by which they could be encouraged and persuaded to go public.